Molecular dynamics study on doping defected graphene by boron. Issue 6 (2nd June 2016) - Liu, Chen; Jin, Enze; He, Shihong; Luo, Shuai; Lin, Mu
ABSTRACT: Boron doping brings remarkable features and modified properties to graphene. In this study, we used molecular dynamics simulations to investigate the influence of vacancies on the graphene boron doping process. The existence of vacancies increases the boron content of doped graphene sheet. The physical mechanisms behind this phenomenon are discussed. The vacancy concentration of graphene affects the formation energy of boron-vacancy pair, the collision frequency between boron atoms and graphene sheet and also affects the boron atom capture cross section of graphene. We have also investigated the boron doping process for bicrystalline graphene. The results reveal that boron atoms tend to be adsorbed on the grain boundary region. The mechanical properties of the boron doped bicrystalline graphene are enhanced compared with the undoped graphene.